Hospitalitynetwork-інноваційна технологія туристичних подорожей - Басюк, Дарія Іванівна (My University, 2013)
Hospitality Network (Hospitalitynetwork) - an association of people offering to stay at home to other members of this community. The idea of ​​hospitality exchange was implemented in 1949, the international non-profit service ServasOpenDoors, whose mission formulated as "world peace". The next year there was a service «Intervac», the priority of which were cheap trip. With the advent of the Internet number and variety of these specialized sites increased, the most popular are : CouchSurfing, HospitalityClub, Bewelcome, Placetostay, Flatjump. In addition to universal networking association are targeted to specific groups of people: bicyclists (WarmShowers), Esperanto (PasportaServo).
Keywords: туризм; гостинність; технології; кафедра туристичного та готельного бізнесу; tourism; hospitality; technology